Oral Prednisolone, Apremilast and Human Umbilical Cord Mesenchymal Stem Cells in the Management of Pemphigus Foliaceus - Zhu Y; Zhang Q; Wu D; Jiang R; Chen L; Chen J (Journal of Inflammation Research)
Yue Zhu,1,* Quanhong Zhang,1,* Dongcheng Wu,2 Ruili Jiang,1,3 Liuqing Chen,1,3 Jinbo Chen1,3 1Department of Dermatology, Traditional Chinese and Western Medicine Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China; 2R&D Center, Wuhan Hamilton Biotechnology Co., Ltd, Wuhan, Hubei, People’s Republic of China; 3Hubei Province & Key Laboratory of Skin Infection And Immunity, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinbo Chen, Department of Dermatology, Traditional Chinese and Western Medicine Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Zhongshan Avenue 215, Qiaokou District, Wuhan, Hubei, 430022, People’s Republic of China, Email chen999jb@163.comAbstract: This case report showed a 60-year-old male with Pemphigus foliaceus (PF), complicated by hypertension, diabetes, and hepatitis B, for whom traditional treatments posed potential risks. The regimen included prednisone, human umbilical cord mesenchymal stem cells (UC-MSCs), and apremilast, showing several advancements: UC-MSCs addressed PF and comorbidities without reported side effects, accelerated steroid tapering substantially compared to apremilast monotherapy, and held superior benefits over hematopoietic stem cells. Over a 4-month follow-up, there was a marked improvement in the patient’s condition, normalization of autoantibody levels, and an increase in regulatory T cells. Further research and extended monitoring are warranted to ascertain the findings’ validity and applicability.Keywords: autoimmune bullous diseases, stem cells, apremilast, regulatory T cells